(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Digitalization of education: is AI and Chat GPT a solution?In recent years, the landscape of education has undergone a profound transformation due to the rapid advancement of digital technologies. One of the most intriguing avenues in this evolution is the integration of Artificial Intelligence (AI) and Chatbots like GPT, which have the potential to revolutionize the way education is imparted and received. By analysing the benefits and limitations of these technologies, this study aims to provide insights into the effectiveness of AI-driven educational tools, their impact on student engagement, and their ability to enhance personalized learning experiences. Additionally, ethical considerations of relying extensively on AI and Chat GPT in education are discussed. The study presented in this paper was conducted on BA and MA students enrolled at the Faculty of Humanities and Social Sciences within Aurel Vlaicu University of Arad, Romania.